Precarization in the Name of Freedom: Material Conditions for Early Independent - Farcas, Liliana; Holgersson , Helena (Nordic Theatre Studies, 2023)
This article is written within the frame of the interdisciplinary research project “Expansion and Diversity: Digitally Mapping and Exploring Independent Performance in Gothenburg 1965–2000”. It contributes to the critical ambition of producing an inclusive historiography of local independent performing arts groups by exploring the municipal distribution of cultural grants and the material conditions in the field. Based on interviews with nine well-known members of early independent performing arts groups in Gothenburg, complemented with archived funding applications and news articles, the article uses a cultural studies perspective to elaborate on how artistic freedom was negotiated in relation to dependence on public funding.